A convergence proof for local mode filtering - Shuoyan Zhang (Elsevier, 2021)
In this paper, we present a convergence proof for an iterative procedure of local mode filtering. We formulate the local mode filtering as a quadratic optimization problem based on the Legendre transform of convex function, from which two closed-form expressions at each iteration step are derived for variables to be optimized. Those analytical solutions ensure that the value of objective function increases monotonically with the progress of the iterative procedure. We also show experimental results using a grayscale image, which support our theoretical results practically.